Assignment of Appropriate Conditions for Synthesizing Tungsten Nanopowder by Electric Explosion of Conductors; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Zhuravkov S. P. Sergey Petrovich; Pustovalov A. V. Aleksey Vitalievich; Kuznetsov M. A. Maksim Aleksandrovich; Rosliy I. S.; Zernin E. A. Evgeny Aleksandrovich (2016, 2016)
Title screen